Pelatihan dan Pembinaan Da’i Cilik TK/TPA Masjid Jami Ushuluddin Di Desa Bacu Kecamatan Tonra - Irdawati; Sri Permata; R. Nurhayati; Sudirman P; Agus Swito (PENDIMAS: Jurnal Pengabdian Masyarakat, 2022)
TK/TPA training and coaching is very important, especially for children or santri and female student. Bacu village, Tonra subdistrict, is a village located in the south of Tonra subdistrict, Bone district, which has not been touched by the existence of training and coaching programs on dai-dai’yah focused on TK/TPA. The purpose of this activity is to regenerate the sprit of self-confidence to appear in public. The achievement of training and coaching dai is to produce generations who have good morals in the future and provide understanding to children about religious knowledge so that they can produce generations who have broader and better Islamic insight, and childrent’s maturity in thinking and acting to improve teh guality of the santri and female students.